PKP-008 Improving the quality of clinical decision making based on total phenytoin serum levels. (24th March 2015) - Juvany, R; Colls, M; Dastis, M; Santulario, L; Leiva, E; Cobo, S; Dot, D; Jódar, R
Abstract : Background: Therapeutic drug monitoring of phenytoin is commonly done by measuring the total phenytoin level (TPHEL) in serum or plasma. This result can be misleading in patients with serum albumin <44 g/L needing correction before use in clinical decision-making. However, serum albumin isn't always requested with phenytoin measurement. Purpose: To design and implement an algorithm, in agreement with the Clinical Laboratory, that includes the albumin serum measurement whenever TPHEL is requested in routine testing in hospitalised patients, in order to facilitate the correct interpretation of TPHEL. Material and methods: Retrospective observational study of hospitalised patients whose TPHEL was determined between January 2013 and August 2014. The algorithm triggers serum albumin analysis in routine testing if it isn't requested on the same day as phenytoin measurement. Variables collected were age, sex, TPHEL, albumin, creatinine and urea. Albumin-adjusted total phenytoin level (AATPHEL) by the Sheiner-Tozer equation and GFR by CKD-EPI were calculated. Phenytoin therapeutic interval considered was 10–20 mg/L. TPHEL and AATPHEL results was classified into infra, supra or therapeutic groups and discrepancies among groups were analysed. Results: 561 TPHEL results were studied (206 patients; average age: 60.5 years; 119 female). 74 (13%) TPHEL did not have albumin results because were stat requests. 98.8% of TPHEL (481 out of 487) had serum albumin <44 g/L and required correction and 93% of them (449 out of 481) had GFR >25 mL/min/1.73 m 2 . Based on the TPHEL alone, 44% required an increased dose while only 27% required it when using AATPHEL. In contrast, 16% of TPHEL results taken alone required dose reduction, which jumped to 38% when the AATPHEL was used. Conclusion: The majority of hospitalised patients had albumin inferior to 44 g/L, requiring the calculation of AATPHEL to optimise clinical decisions. The collaboration between the Clinical Laboratory and the Pharmacy Service has facilitated the availability of serum albumin values for nearly 90% of TPHEL thus improving quality in TPHEL interpretation. Reference: Winter. Basic Clinical Pharmacokinetics 2004 No conflict of interest.